Development and evaluation of an electrochemical DNA based magnetic nanoparticle biosensor for detecting the fungal pathogen fusarium oxysporum f. sp. cubense - Akwuruoha, Uzoma Nobel (Stellenbosch : Stellenbosch University, 2024)
Thesis (MEng)--Stellenbosch University, 2024.